2009
DOI: 10.1111/j.1365-2133.2009.09034.x
|View full text |Cite
|
Sign up to set email alerts
|

An ‘n-of-1’ placebo-controlled crossover trial of intravenous immunoglobulin as adjuvant therapy in refractory pemphigus vulgaris

Abstract: The results of this study confirm a beneficial effect of IVIg in the management of refractory PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…One Japanese study showed a reduction in disease severity and autoantibody titres as measured by enzyme-linked immunoassay (ELISA) in patients who received a single dose of IVIG (11). The second study showed a reduction in autoantibody titres and improvement in subjective disease scores after a single cycle of IVIG (12).…”
mentioning
confidence: 99%
“…One Japanese study showed a reduction in disease severity and autoantibody titres as measured by enzyme-linked immunoassay (ELISA) in patients who received a single dose of IVIG (11). The second study showed a reduction in autoantibody titres and improvement in subjective disease scores after a single cycle of IVIG (12).…”
mentioning
confidence: 99%
“…The patient underwent two phases of treatment consisting of 6 consecutive months of either IVIG or placebo infusion in conjunction with prednisolone and azathioprine. 39 IVIG has an excellent safety profile in comparison with other treatment modalities for pemphigus, with mild side effects that include headache, fever, chills, myalgia, flushing, hypotension, tachycardia, and gastrointestinal symptoms. 11 Additionally, it should be noted that a recent case series of eight pregnant patients with PV who were treated with IVIG showed a good response, without any apparent signs of complications from treatment in the mother or the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…11 The September/October 2014 literature is replete with case reports of refractory PV responding to rituximab and there is growing interest in the use of IVIG. [32][33][34][35][36][37][38][39][40][41] Though no rituximab-dosing protocol is clearly superior, giving 4 weekly 375 mg/ m 2 doses allows for more rapid redosing and would be more suitable for incorporating IVIG therapy if needed. IVIG is an appropriate option when an increased risk of infection cannot be tolerated because IVIG, theoretically, also confers immunoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events were similar between the three groups. Another IVIg study also showed a beneficial effect in pemphigus [19]. The limitation of these studies was their short-term follow-up, so that relapse rates could be compared with other options.…”
Section: Therapies Used In Pemphigus Main Textmentioning
confidence: 99%